EXAMINE THE ROLE OF WORK ETHIC IN STRENGTHENING THE INFLUENCE OF WORK-LIFE BALANCE AND COMPETENCE ON EMPLOYEE PERFORMANCE - Reky Arif Rahman; Budi Santoso; Haris Hermawan (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The Probolinggo Correctional Institution Class IIB plays a vital role in the implementation of correctional functions. Employee performance is a key factor in the success of any institution; therefore, work-life balance and competence are considered crucial in influencing work ethic and overall productivity. This study aims to examine the impact of work-life balance and competence on the performance of employees at Probolinggo Class IIB Prison, as well as the mediating role of work ethic in this relationship. The research employed a quantitative survey approach, involving a sample of employees from Probolinggo Class IIB Prison. Data were analyzed using Structural Equation Modeling (SEM) with the WarpPLS statistical tool. The results indicate that work-life balance and competence have a positive and significant effect on employee performance. Additionally, work-life balance and competence positively and significantly influence employee work ethic. Work ethic was found to mediate and strengthen the relationship between work-life balance, competence, and performance improvement. Therefore, work ethic is a critical factor linking competence and work-life balance to the performance of prison employees. It is recommended that prison management implement ongoing programs that support work-life balance and competency training to achieve optimal professionalism and productivity.